THE "CLASS" DISSENSION OF COLONIAL PERIOD IN SUNDANESE NOVELS: REVIEW OF IDENTITY POLITICS - Asep Yusup Hudayat (LITERA, 2020)
The culture of feudalism and democracy in the Dutch East Indies agreed to oppose one another. The intersection of the two cultures is the perspective of indigenous and colonial identity which ultimately demands a struggle to demand its "class" rights. The struggle for narratives of power was inevitable. The first Sundanese novel Baruang ka nu Ngarora “Poison for the Youth” (1914) by D.K. Ardiwinata and Gogoda ka nu Ngarora “Temptations for the Youth”(1951) as a novel response from M.A. Salmun has shown these oppositional phenomena. This study aims to trace the struggle for narration that has implications for identity politics in the Dutch East Indies colonial period. The method used in this study is descriptive analysis from the perspective of postcolonial studies. From a postcolonial perspective, literary works have become an important means for tracking colonialism practices where the narratives of dominant and defensive forces are nested. The results of the analysis show that the narrative of class disagreement in Gogoda ka nu Ngarora is used as a motive for empowering the spirit of democracy, in Baruang ka nu Ngarora, is used as a motive for the assertion of partiality towards feudal culture. Through the spirit of democracy, the struggle for identity politics was built by M.A. Salmun in Gogoda ka nu Ngarora to rejects feudal ideologies. Through a feudal spirit, identity politics was built D.K. Ardiwinata in Baruang ka nu Ngarora to establishing class identity.Keywords: identity politics, class, native, colonialPERTENTANGAN "KELAS" PADA MASA KOLONIAL DALAM NOVEL SUNDA: TINJAUAN POLITIK IDENTITASAbstrak Budaya feodalisme dan budaya demokratis pada masa kolonial Hindia Belanda seringkali menunjukkan pertentangan satu dengan lainnya. Persinggungan kedua budaya tersebut dipengaruhi sudut pandang tentang identitas pribumi dan kolonial yang akhirnya memicu perjuangan menuntut hak-hak "kelas"-nya. Perebutan narasi kekuasaan pun tidak dapat dihindarkan. Novel Sunda pertama Baruang ka nu Ngarora (1914) karangan D.K. Ardiwinata dan novel sambutannya Gogoda ka nu Ngarora (1951) karangan M.A. Salmun telah menunjukkan fenomena-fenomena pertentangannya tersebut. Studi ini bertujuan menjejak perebutan narasi yang berimplikasi kepada upaya politik identitas pada masa kolonial Hindia Belanda. Metode yang digunakan dalam studi ini adalah deskriptif analisis dalam perspektif studi postkolonial. Berdasarkan perspektif postkolonial, karya sastra menjadi sarana penting untuk menjejak praktik kolonialisme tempat bersarangnya narasi-narasi kekuasaan dominan dan perlawanannya. Hasil analisis menunjukkan bahwa narasi pertentangan kelas dalam Gogoda ka nu Ngarora digunakan sebagai motif pemberdayaan semangat demokrasi, dalam Baruang ka nu Ngarora digunakan sebagai motif penegas keberpihakan terhadap budaya feodal. Melalui semangat demokrasi, upaya politik identitas dibangun M.A. Salmun dalam Gogoda ka nu Ngarora untuk menolak ideologi-ideologi feodal. Melalui semangat feodal, politik identitas dibangun D.K. Ardiwinata dalam Baruang ka nu Ngarora untuk mengukuhkan identitas kelas.Kata kunci: politik identitas, kelas, pribumi, kolonial